Self-Reported Weight and Height for Evaluating Obesity Control Programs - Dhaliwal, Satvinder; Howat, Peter; Bejoy, Thaila; Welborn, T. (PNG Publications, 2010)
Objectives: To assess the adequacy of self-reported weight and height as indicators for BMI in community basedobesity control programs. Methods: Self-reported and measured weight and height and calculated BMI in 6979 adults were assessed using analysis of covariance. Results: Prevalence of obesity (BMI>25kg/m2) and overweight (25-29.9kg/m2) was lower using selfreported values by 3.2% and 5.0%, respectively. Females underreported BMI more than males did; and older subjects, more than younger subjects. Conclusions: Self-reported weight and height measurements may be used for the evaluation of community-based obesity control programs with the application ofcorrection factors. This will minimize costs associated with physical measurements.